Rheological and thermal properties of palm kernel shell filled low density polyethylene composites - Lim, Bee Ying (School of Materials Engineering, 2013)
The study was focused on the rheological and thermal properties of palm kernel shell (PKS) filled low density polyethylene (LDPE) composites. Several different chemicals were added into the composites or treated with the filler prior to compounding process.